PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR PAI ANAK DI JORONG KUBANG BALAMBAK, KECAMATAN MUNGKA - Intan Kurniati (El-Rusyd, 2021)
Research moves from the phenomenon experienced by parents in Wallow Balambak. Where there are most parents who do not pay attention to the importance of education, especially on learning Islamic Religious Education. This study aims to express: There's no influence on parents’ education levels on significant learning motivation. Using the deskritifkuatitatif method. This study is classified as a correlation research that connects two different variables.The population in this study were the parents graduated from D3 and S1 a number of 34 People. Purposive sampling research sample is a determination technique for certain considerations.Data was collected by using a questionnaire Likert questionnaire and the data analysis technique used simple statistic. The correlater of research variables use the Product Moment formula, with data analysis techniques using Statistical Product and Service Solution (SPSS) Version of 26.There is significance to the effect of learning activity with learning results is 0.00, meaning because of its value <0.05 can be said that there is a relationship between parent educational level of motivation to learning motivation. And it can be known that the value of the pearson Correlation is 80.6%. It can be known the influence between pendidkan levels and the learning motivation is the perfect Correlation. Because what affects the motivation of learning is tingakat parents’ education. And the correlation positively effect.